OP0069 The burden of ankylosing spondylitis: a population based study. (15th June 2017) - Lee, JS; Lee, HY; Lee, EE; Song, YW; Lee, EY
Abstract : Background: Ankylosing spondylitis (AS) is an inflammatory rheumatic disease with musculoskeletal and systemic manifestations. Because AS is typically diagnosed before the age of 40 years and follows a chronic progressive course, its impact on the patient is life-long. In addition to the burden on the individual patient, that on the society is also increasing cumulatively every year [1]. The burden of AS is not confined to healthcare cost spent due to back pain and stiffness of the disease itself [2–4], but also encompass extra-articular manifestation (EAM), comorbidities, disability, and mortality contributed from AS [5]. Objectives: This study aimed to evaluate the disability, mortality, and healthcare cost for quantifying the burden of AS. Methods: We conducted a nationwide population-based study based on national health insurance data in Korea. The patients with incident AS (n=1111) were identified with controls (n=5555) who were matched by age, sex, income, and geographic region from the year 2003 to 2013. EAMs, comorbidities, mortality and type and severity of disabilities were presented as incidence rate and compared to the controls as incidence rate ratios (IRRs). Annual health expenditure per patient was analyzed by the year and relation to AS. Results: During the follow-up, 28% of patients in this cohort experienced any kind of EAM. More comorbidities with Charlson comorbidity index ≥3 (OR 2.18, 95% CI 1.91 to 2.48) were significantly associated. Disability rate was higher than controls regardless of causes and severity (OR 2.94, 95% CI 2.48 to 3.48). Crude IRRs for mortality was not significantly increased, but by multivariate analysis, older age at diagnosis (≥45 years old) (OR 10.53, 95% CI 4.31 to 25.68) was most strongly related to increased disability and mortality rates (Fig.1 ). Biologic agents elevated annual health expenditures of AS but decreased AS unrelated costs (mean 1112 vs 877 USD, p=0.0068) (Fig.2). Conclusions: Along with demographic factors, systemic consequences such as EAMs and other comorbidities were associated with increased disabilities and healthcare expenditures in AS. Older age at diagnosis was significantly associated with increased mortality rates. References: The Korean center for disease classification and information, disease statistics section, http://www.koicd.kr/stat/diseaseStats.do (Page in Korean). Huscher D, Merkesdal S, Thiele K, et al. Cost of illness in rheumatoid arthritis, ankylosing spondylitis, psoriatic arthritis and systemic lupus erythematosus in Germany. Annals of the rheumatic diseases 2006;65(9):1175–83 doi: 10.1136/ard.2005.046367[published Online First: Epub Date]|. Franke LC, Ament AJ, van de Laar MA, et al. Cost-of-illness of rheumatoid arthritis and ankylosing spondylitis. Clinical and experimental rheumatology 2009;27(4 Suppl 55):S118–23. Cooksey R, Husain MJ, Brophy S, et al. The Cost of Ankylosing Spondylitis in the UK Using Linked Routine and Patient-Reported Survey Data. PloS one 2015;10(7):e0126105 doi: 10.1371/journal.pone.0126105[published Online First: Epub Date]|. Boonen A, van der Linden SM. The burden of ankylosing spondylitis. The Journal of rheumatology Supplement 2006;78:4–11. Acknowledgements: None. Disclosure of Interest: None declared